Increased Levels of Cortisol in Individuals With Suicide Attempt and Its Relation With the Number of Suicide Attempts and Depression - Genis-Mendoza, Alma Delia; Dionisio-García, Diana María; Gonzalez-Castro, Thelma Beatriz; Tovilla-Zaráte, Carlos Alfonso; Juárez-Rojop, Isela Esther; López-Narváez, María Lilia; Castillo-Avila, Rosa Giannina; Nicolini, Humberto (Frontiers in Psychiatry, 2022)
Background. Abnormalities in the hypothalamic-pituitary-adrenal axis (HPA) have been reported in individuals with suicide behavior. The aim of the study was to evaluate cortisol levels in peripheral plasma of individuals with more than one suicide attempt. Methods. Cortisol concentrations in peripheral plasma were measured using the ELISA technique. Suicide attempts were evaluated by the Columbia Suicide Severity Rating Scale, while depression was evaluated by the Hamilton Depression Rating Scale. Results: We found elevated cortisol levels in the suicide attempt group when compared with healthy controls (F=7.26, p value= 0.008), but no statistical differences with the psychiatric diseases group (F=1.49, p value=0.22). Cortisol levels were higher in individuals with depression (F=8.99, P=0.004) and in individuals with two or more suicide attempts (F=13.56, P<0.001). Conclusions: Cortisol levels are increased in individuals who attempt suicide and higher of cortisol concentrations in plasma regard to depression and more attempts of suicide.